Play Dead: Andy Carpenter #6 - Rosenfelt, David (New York : Warner Books, 2007)
"Author David Rosenfelt's hero, Andy Carpenter, plunges into a high-profile murder case with a golden retriever as his key witness"--Provided by publisher.
Keywords: Carpenter, Andy (Fictitious character) -- Fiction; Attorney and client -- Fiction; Trials (Murder) -- Fiction; New Jersey -- Fiction; Detective and mystery stories; Legal fiction; Detective fiction; Mystery fiction